Double Burden Trap: Poverty of Sandwich Households in Bengkulu Province - Guntur Nugroho; Nurlatifah Nurlatifah (CV. Green Publisher Indonesia, 2026)
The phenomenon of sandwich households those bearing dual economic burdens both upwards and downwards across generations has the potential to increase socio-economic vulnerability, yet remains underexplored in poverty-related studies. This research aims to analyze the characteristics of sandwich households and the factors influencing their poverty status in Bengkulu Province in 2024. Utilizing data from the 2024 National Socio-Economic Survey and a multinomial logistic regression approach, this study classified sandwich households into four economic status categories: poor, vulnerable-to-poverty, moving toward the middle-class, and middle-class. The findings reveal that households headed by individuals aged over 35, working as informal workers, having more than four dependents, and receiving social-economic assistance are more likely to fall into the poor and vulnerable-to-poverty groups. In addition, the low educational attainment of the household head significantly increases the risk of falling into the vulnerable category. These results indicate that there are opportunities for targeted policy interventions focusing on these at-risk groups through skills training, improved access to formal employment, and better-targeted social-economic assistance programs. Moreover, enhancing educational quality represents a vital long-term strategy to break the cycle of intergenerational economic vulnerability within sandwich households.